Analisis Minat Baca Peserta Didik di Sekolah Dasar: Studi Kasus di SDN Klagen, Sidoarjo - Yulistiani, Dini Fadilisma; Nuroh, Ermawati Zulikhatin (Jurnal Gentala Pendidikan Dasar, 2026)
Students’ reading interest still faces many challenges, even though literacy programs have been implemented in schools. In reality, reading is often treated as an academic task rather than a meaningful activity. Many students read only when they have tests or assignments, which shows that their motivation is mostly external. As a result, their inner motivation to read has not fully developed. This study aims to understand reading interest from students’ own perspectives, especially how they experience reading in their daily lives. It not only focuses on how often students read, but also how they feel and give meaning to literacy activities. This research uses a qualitative case study conducted in a sixth-grade class at SDN Klagen Sukodono, Sidoarjo. Data were collected through interviews, observations, and documentation, and then analyzed with respect to the affective, behavioral, cognitive, and social aspects of reading engagement. The findings show that students are more engaged when reading is enjoyable and supported by good habits, helpful strategies, and a positive learning environment. However, their reading habits are still inconsistent and often depend on external support. Therefore, fostering students’ intrinsic motivation requires a more meaningful and supportive literacy environment.